The types of investments in the scope of startups (Research, Society and Development, 2021)
The present study analyzes some notes about the type of investments in the scope of startups, especially with regard to economic growth and the best way to invest, considering that in a completely unknown and uncertain business model, but which has great profit potential, scalable and disruptive. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of documentary and bibliographic data, proceeded in order to carry out a thorough analysis of the normative framework that deals with startups. Notwithstanding, the extreme perfection of the legal aspect in the business field was pointed out, as a way of making possible the protection, security and business quality for financing, seeking to develop the Brazilian startups ecosystem. Thus, in view of the exposed problems, it was sought to clarify that a startup needs third party capital to start operating. In addition, the degree of relationship between the investor and the investee in this quality of financing was highlighted, especially with regard to the angel investor and the traditional investor.